About the Teyt-Shafarevich product in elliptical curves over pseudolocal fields with remainder fields of the characteristics 3 - Andriichuk , V. I. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Letk be a general local field with pseudolocal residue field κ, char κ = 3, and А an elliptic curve defined over k. It is proved that the Tate-Shafarevich product H^1(k, A) × A_k→ Q/ Z of the group H^1 (k, А) of principal homogeneous spaces of the curve А over k and the group А_к of its k-rational points is left nondegenerate.